Analysis Of Shoe Product Quality Control At PT XYZ: Analisis Pengendalian Kualitas Produk Sepatu Di PT XYZ - Arzaq, Miftah; Arzaq Rahmansyah, M. Miftah; Wulandari, Indah Apriliana Sari (Universitas Muhammadiyah Sidoarjo, 2024)
PT XYZ is a company located in East Java, Indonesia. The company is engaged in manufacturing footwear such as shoes and sandals using the latest technology, namely injection molding. As a company engaged in the field of footwear, of course PT XYZ always prioritizes quality control to ensure the quality of products that have been produced by not neglecting quality control in every production process. The daily production capacity of PT XYZ using 7 machines is 2000 - 3000 pairs of shoes for each machine and, if 7 machines then the production that can be produced in 1 day can range from 15,000 - 21,000 pairs every day. With a very high production capacity PT XYZ still controls the quality of shoes using the six sigma method.